ON SOME ECONOMIC MODELS SOLVABLE USING THE PARABOLIC MODEL OF THE LEAST SQUARES METHOD - CĂTĂLIN ILIE MITRAN (Annals of the University of Petrosani: Economics)
Many of today’s techno-economic problems can be modeled by various mathematical methods. One of the best known and most applied is the so-called approximation tchnique by the method of the smallest squares.The best known caseof this approximationmethod is the linear one.The present paper is dedicatedto another case of this method, namely the parabolic one.Initially, the main aspects related to the parabolic function and the method of the smallest squares will be presented, the parabolic case, after which a numerical example of calculation to exemplify the application of the method of the smallest squares, the parabolic case. Finally, two such applications of the mentioned method will be analyzed in approximation and estimation of the evolution of some economic indicators within the indicators dedicated to the circular economy indicators.